Estimation and prediction for an inverted exponentiated Rayleigh distribution under hybrid censoring. Issue 7 (3rd April 2018) - Kayal, Tanmay; Tripathi, Yogesh Mani; Rastogi, Manoj Kumar
ABSTRACT: In this paper we consider estimation of unknown parameters of an inverted exponentiated Rayleigh distribution when it is known that data are hybrid Type I censored. The maximum likelihood and Bayes estimates are derived. In sequel interval estimates are also constructed. We further consider one- and two-sample prediction of future observations and also obtain prediction intervals. The performance of proposed methods of estimation and prediction is studied using simulations and an illustrative example is discussed in support of the suggested methods.